2014
DOI: 10.1186/1471-2407-14-891
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Wnt activity during colorectal cancer progression through selective hypermethylation of Wnt signaling antagonists

Abstract: BackgroundThere is emerging evidence that Wnt pathway activity may increase during the progression from colorectal adenoma to carcinoma and that this increase is potentially an important step towards the invasive stage. Here, we investigated whether epigenetic silencing of Wnt antagonists is the biological driver for this increased Wnt activity in human tissues and how these methylation changes correlate with MSI (Microsatelite Instability) and CIMP (CpG Island Methylator Phenotype) statuses as well as known m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 41 publications
5
51
1
3
Order By: Relevance
“…These tumor suppressor genes were shown to be regulated by methylation in the previous studies. 29,36 However, the level of promoter methylation of these genes in colon cancer cell lines in SW480 and HCT116 was significantly higher than that of HUVEC. Surprisingly, DNMT3B only decreased promoter methylation of SFRP1, SFRP2, DKK2 and WIF1 genes and did not alter the methylation levels of CDK2N2A, CACN2A and hMLH1.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These tumor suppressor genes were shown to be regulated by methylation in the previous studies. 29,36 However, the level of promoter methylation of these genes in colon cancer cell lines in SW480 and HCT116 was significantly higher than that of HUVEC. Surprisingly, DNMT3B only decreased promoter methylation of SFRP1, SFRP2, DKK2 and WIF1 genes and did not alter the methylation levels of CDK2N2A, CACN2A and hMLH1.…”
Section: Discussionmentioning
confidence: 96%
“…For example, while some of these tumor suppressor genes can be methylated by DNMT-1, others are target of DNMT3. 36 Regulation of these well-known tumor suppressor genes (hMLH1, CDK2N2A and CACN2A) by other methyl transferases should be validated in future studies. Among tumor suppressor genes, it was shown that WIF1 was the most sensitive one to the effect of DNMT3B since in HCT-339, with no observed downregulation of DNMT3B, the methylation level of WIF1 was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Régóta ismert, hogy bizonyos, vastagbéldaganatokban azonosított hipermetilált gének, például egyes tumorszuppresszor gének inaktivációja fokozza a sejt proliferációt, így szelektív előnyt jelenthet a tumorsejtek számára [69,70]. Az 1. táblázat a vastagbéldaganatok-ban legfontosabb hipermetilált tumorszuppresszor markereket foglalja össze [71][72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Lokális Hipermetilációunclassified
“…25 CpG methylation of Wnt antagonists such as SFRP5, SFRP1, SFRP2, Dickkopf Wnt signaling pathway inhibitor 2, Wnt inhibitory factor 1, wingless-type MMTV integration site family, member 3A, and SRY (sex determining region Y-box 17) were shown to significantly increase in the transition from normal tissues to adenoma. 27 Moreover, Wnt inhibitory factor 1, SFRP1, SFRP2, and Dickkopf Wnt signaling pathway inhibitor 2 were hypermethylated during transition from adenoma to carcinoma. Therefore, stepwise selective hypermethylation of several Wnt antagonists increases the expression of Wnt target genes during development of colon carcinoma.…”
Section: Wnt Antagonistsmentioning
confidence: 99%
“…Therefore, stepwise selective hypermethylation of several Wnt antagonists increases the expression of Wnt target genes during development of colon carcinoma. 27 Wnt signaling may be modulated by Wnt antagonists that interact with Wnt ligands themselves. For example, expression of SFRP5 and SFRP1 was markedly reduced in HBx-infected cells.…”
Section: Wnt Antagonistsmentioning
confidence: 99%